ANALISIS TEORITIS KOMITMEN KARYAWAN: KAJIAN KOMPREHENSIF STRATEGI PENGEMBANGAN LOYALITAS ORGANISASI - Ade Setiawan; Wahyudi; Tuti Hasanah; Ayu Kusuma Wardani; Hadi Supratikta (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This theoretical analysis examines the conceptual frameworks and scholarly perspectives on employee commitment in organizations, synthesizing current literature to develop a comprehensive understanding of commitment-building strategies. Through an extensive review of contemporary organizational behavior theories, we explore the multifaceted nature of employee commitment and its theoretical implications for organizational success. The study analyzes various theoretical models of employee commitment, identifying key constructs and their interrelationships. The analysis reveals that employee commitment is conceptualized through multiple theoretical lenses, including social exchange theory, organizational support theory, and the job demands-resources model. This paper contributes to the academic discourse by proposing an integrated theoretical framework for understanding and developing employee commitment, considering both individual psychological factors and organizational contextual elements.This study examines the evolution of employee commitment concepts within the modern business context, focusing on theoretical frameworks including Social Exchange Theory, Organizational Support Theory, and the Job Demands-Resources Model. Employee commitment is regarded as a critical element for organizational success and stability, encompassing affective, continuance, and normative dimensions. In addition to psychological factors, work environment, and job satisfaction, the research highlights the need for a holistic approach in strategies to develop employee loyalty. Through a literature analysis, this study aims to provide comprehensive insights and strategic recommendations for enhancing employee engagement and retention within organizations.Keywords: employee commitment theory, organizational loyalty, theoretical framework, organizational behavior, workplace psychology